SCREENING OF COMPOUNDS ARTOCARPUS ALTILIS AS ANTICANCER COLORECTAL AGAINST EGFR RECEPTOR THROUGH MOLECULAR DOCKING - Mochammad Erwinsyah Iham; Muhammad Fauzi; Juwita Ramadhani (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
According to WHO, cancer is the uncontrolled growth and spread of cells, while according to the NCI (National Cancer Institute) it is a disease in which abnormal cells divide uncontrollably and can attack the surrounding tissue. Colorectal cancer is a malignant tumor that arises from the epithelial tissue of the colon or rectum. Colorectal cancer refers to malignant tumors found in the colon and rectum. The standard drug compound used is cetuxinab, a colorectal cancer therapy drug, a flavonoid derivative compound from the breadfruit plant as a test ligand. The receptors used for molecular docking analysis were obtained from the Protein Data Bank (PDB) at http://www.rcsb.org/pdb/. The receptor used to predict activity is the EGFR receptor GDP code 4I22. Breadfruit plants contain various secondary compounds, such as flavonoids, phenolics, saponins, tannins, polyphenols, hydrocyanic acid, acetylcholine, riboflavin. The compounds used are 20 flavonoid compounds contained in breadfruit plants, including Artocarpin, Lysopine, Quarcetin, Morusin, Isocylomulberrin, Cyloaltilisin, Artonin-E, Cyloaltilisin-7, Cylocommunol, Cyclomorusin, Cyclomulberrin, Cyloartobiloxanthone, Isoclyclomorusin, Lupeol acetate, Artonin f, Cycloartomunin, Artocarpesin, Artocommunol ca, Artonol d, Artocommunol cc. three compounds that show good affinity for the EGFR receptor.